Bell’s palsy due to congenital cholesteatoma of petrous apex: a case report - Zulkifli, Muhd Faiz Bin; Saim, Lokman Bin (Bangladesh Medical Journal, 2019)
Congenital cholesteatoma (CC) is a rare disease, it accounts for 2-5% of all cholesteatomas [2] most common site being middle ear. Case report: We reported a case of 23-year-old female presented with progressive left sided facial asymmetry for 4 years and progressive hearing loss in the left ear for 2 years. She had normal left tympanic membrane and complete left lower motor neuron facial nerve palsy. High resolution computed tomography with contrast temporal bone showed extensive bony destruction, petrous apex and soft tissue lesion. Patient then proceed with transmastoid translabyrinthine approach. Diagnosis of cholesteatoma confirmed by histopathological examination (HPE). Congenital cholesteatoma of petrous apex is a rare case. It is a challenge to diagnose congenital cholesteatoma pre-operatively without specific radiological sign. This is because the disease is generally difficult to differentiate with mucocele and cholesterol granuloma on CT scan. Therefore, intraoperative diagnosis more accurate rather than the preoperative diagnosis. Bangladesh Med J. 2018 Jan; 47 (1): 41-43